Tax havens how globalization really works - Palan, Ronen (Ithaca Cornell University Press, 2010)
From the Cayman Islands and the Isle of Man to the Principality of Liechtenstein and the state of Delaware, tax havens offer lower tax rates, less stringent regulations and enforcement, and promises of strict secrecy to individuals and corporations alike. In recent years government regulators, hoping to remedy economic crisis by diverting capital from hidden channels back into taxable view, have undertaken sustained and serious efforts to force tax havens into compliance.
Includes bibliographical references and index.
Keywords: Tax havens